Odpowiedzi

2010-03-10T20:19:40+01:00
2(5a-3)-a-4(3a-2)=0
10a-6-a-12a+8=0
10a-a-12a=-8+6
-3a=-2
a=1½

2b-(1-b)-11-b=0
2b-1+b-11-b=0
2b=1+11
2b=12
b=6

3y-2(y-1)=-6
3y-2y+1=-6
y=-6-1
y=-7

3(3-5y)=90-5y(3y-2)
9-15y=90-15y+12
-15y+15y=90+12-9
0=93 (brak rozwiązań)

₂₋₅(x-2)-x+4=0
2-5x+10-x+4=0
-5x-x=-4-10-2
-6x=-16
x=2⅔

¹⁻⁴z+(z-6)=₂₋₃(z-2)
1-4z+z-6=2-3z+6
4z+z+3z=2+6-1+6
8z=13
z=1 4/13
11 2 11
2010-03-10T20:32:29+01:00
A) 2(5a-3)-a-4(3a-2)=0
10a-6-a-12a+8=0
10a-a-12a=6-8
-3a=-2 /podzielić -3
a=0,67

b)2b-(1-b)-11-b=0
2b-1+b-11-b=0
2b=1+11
2b=12 /podzielić 2
b=6

c)3y-2(y-1)=-6
3y-2y+2=-6
y=-6-2
y=-8

d) 3(3-5y)=90-5y(3y-2)
9-15y=90-15y kwadrat+10y
15ykwadrat-15y-10y=90-9
15ykwadrat-25y=81

e)₂₋₅(x-2)-x+4=0
2-5x+10-x+4=0
-6x=-10-2-4
-6x=-16 /podzielić -6
x=2,67

f)¹⁻⁴z+(z-6)=₂₋₃(z-2)
1-4z+z-6=2-3z+6
-4z+z+3z=2+6-1
0=7 coś chyba jest żle( nie wiem czy to jest minusowa potęga czy tak ci się napisało.Jeżeli minusowa potęga to na pewno żle)






5 2 5